Salmonella Vaccine Study in Oxford (SALVO) trial: protocol for an observer-participant blind randomised placebo-controlled trial of the iNTS-GMMA vaccine within a European cohort - Melita A Gordon; Ellis Owusu-Dabo; Florian Marks; Carsten Mantel; Andrew J Pollard; Brama Hanumunthadu; Rachel White; John A Crump; Hannah Robinson; Jan Jacobs; Samuel Kariuki; Bieke Tack; et al. (BMJ Open)
Introduction Invasive non-typhoidal Salmonellosis (iNTS) is mainly caused by Salmonella enterica serovars Typhimurium and Enteritidis and is estimated to result in 77 500 deaths per year, disproportionately affecting children under 5 years of age in sub-Saharan Africa. Invasive non-typhoidal Salmonellae serovars are increasingly acquiring resistance to first-line antibiotics, thus an effective vaccine would be a valuable tool in reducing morbidity and mortality from infection. While NTS livestock vaccines are in wide use, no licensed vaccines exist for use in humans. Here, a first-in-human study of a novel vaccine (iNTS-GMMA) containing S. Typhimurium and S. Enteritidis Generalised Modules for Membrane Antigens (GMMA) outer membrane vesicles is presented.Method and analysis The Salmonella Vaccine Study in Oxford is a randomised placebo-controlled participant-observer blind phase I study of the iNTS-GMMA vaccine. Healthy adult volunteers will be randomised to receive three intramuscular injections of the iNTS-GMMA vaccine, containing equal quantities of S. Typhimurium and S. Enteritidis GMMA particles adsorbed on Alhydrogel, or an Alhydrogel placebo at 0, 2 and 6 months. Participants will be sequentially enrolled into three groups: group 1, 1:1 randomisation to low dose iNTS-GMMA vaccine or placebo; group 2, 1:1 randomisation to full dose iNTS-GMMA vaccine or placebo; group 3, 2:1 randomisation to full dose or lower dose (dependant on DSMC reviews of groups 1 and 2) iNTS-GMMA vaccine or placebo.The primary objective is safety and tolerability of the vaccine. The secondary objective is immunogenicity as measured by O-antigen based ELISA. Further exploratory objectives will characterise the expanded human immune profile.Ethics and dissemination Ethical approval for this study has been obtained from the South Central—Oxford A Research Ethics Committee (Ethics REF:22/SC/0059). Appropriate documentation and regulatory approvals have been acquired. Results will be disseminated via peer-reviewed articles and conferences.Trial registration number EudraCT Number: 2020-000510-14.